Asynchrony in Peritumoral Resting-State Blood Oxygen Level–Dependent fMRI Predicts Meningioma Grade and Invasion - Wu, P.B.; Chow, D.S.; Petridis, P.D.; Sisti, M.B.; Bruce, J.N.; Canoll, P.D.; Grinband, J. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Meningioma grade is determined by histologic analysis, with detectable brain invasion resulting in a diagnosis of grade II or III tumor. However, tissue undersampling is a common problem, and invasive parts of the tumor can be missed, resulting in the incorrect assignment of a lower grade. Radiographic biomarkers may be able to improve the diagnosis of grade and identify targets for biopsy. Prior work in patients with gliomas has shown that the resting-state blood oxygen level–dependent fMRI signal within these tumors is not synchronous with normal brain. We hypothesized that blood oxygen level–dependent asynchrony, a functional marker of vascular dysregulation, could predict meningioma grade.MATERIALS AND METHODS: We identified 25 patients with grade I and 11 patients with grade II or III meningiomas. Blood oxygen level–dependent time-series were extracted from the tumor and the radiographically normal control hemisphere and were included as predictors in a multiple linear regression to generate a blood oxygen level–dependent asynchrony map, in which negative values signify synchronous and positive values signify asynchronous activity relative to healthy brain. Masks of blood oxygen level–dependent asynchrony were created for each patient, and the fraction of the mask that extended beyond the contrast-enhancing tumor was computed.RESULTS: The spatial extent of blood oxygen level–dependent asynchrony was greater in high (grades II and III) than in low (I) grade tumors (P < 0.001) and could discriminate grade with high accuracy (area under the curve = 0.88).CONCLUSIONS: Blood oxygen level–dependent asynchrony radiographically discriminates meningioma grade and may provide targets for biopsy collection to aid in histologic diagnosis.AUCarea under the curveBOFBOLD outside fractionBOLDblood oxygen level–dependentFOFFLAIR outside fraction